Comparison Between Conventional and Sutureless Thyroidectomy - Kousar Parveen, Sajeela Kokab, Zahra Akhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The main purpose of this study is to compare the outcomes between conventional and sutureless (Harmonic® FOCUS) thyroidectomy. Study Design: Prospective/ Comparison study Place and Duration: de’Montmorency College of Dentistry, Lahore.Nov 2019-Aug 2020 Methods: There were eighty patients of ages 20-70 years were presented in this study. All the patients had multinodular, primary and secondary goitre. Patients provided written consent for the detailed demographics included age, sex and body mass index. The patients were separated into two groups, I and II, for the study. Group I received conventional technique and sutureless technique was used in group II. Outcomes were operative time, hospital stay, blood loss, post-operative drainage volume and complications assessed and compared among both groups. We used SPSS 20.0 version to analyze complete data. Results: In group I 35.34±6.55 years was the mean age with mean BMI 25.15±7.21 kg/m2 and in group II mean age was 36.23±4.31 years with mean BMI 25.15±8.15 kg/m2. There were 25 (62.5%) females and 15 (37.5%) males in group I and in group II 23 (57.5%) females and 17 (42.5%) males. Majority of the patients among both groups had multinodular goitre 32 (80%) and 30 (75%). We found less operative time in group II 60.12±11.52 minutes as compared to group II 81.9±9.34 minutes. Intraoperative blood loss in group I was significant 59.21±7.71 ml as compared to group II 26.4±10.39 ml. Mean drainage volume in group II was lower 10.13±13.23 ml as compared to group I 28.14±5.41 ml. Frequency of complications in group I was higher 5 (12.5%) as compared to group II 3 (7.5%). Conclusion: As a result of this study, we determined that the sutureless thyroidectomy approach was a successful and safe alternative to conventional thyroidectomy in terms of reduced operative time, hospital stay, and post-surgical problems when compared to conventional thyroidectomy.